Policy recommendations - Kaimowitz, D.; Angelsen, A. (CAB International, 2001)
This final chapter of the book offers a set of policy recommendations. It presents some typical win-win outcomes, including technologies suited for forest poor areas, labour intensive technologies promoting intensification to replace land extensive farming practices, and promoting agricultural systems that provide environmental services similar to those of natural forests. It also discusses some typical win-lose outcomes of situations with trade-offs: technologies which require little or displace labour, new products for large markets with abundant labour, eradication of diseases that limit deforestation, and technological progress in forest margin areas with rapidly growing labour forces. The chapter also relates the issues this volume discusses with the current trend towards greater economic liberalisation and globalisation and with the overall policy objectives of poverty reduction and economic growth.